2021
DOI: 10.21037/jtd-20-2568
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of patients with severe COVID-19 at increased risk of in-hospital death: a multicenter case-control study in Wuhan

Abstract: Background: Most evidence regarding the risk factors for early in-hospital mortality in patients with severe COVID-19 focused on laboratory data at the time of hospital admission without adequate adjustment for confounding variables. A multicenter, age-matched, case-control study was therefore designed to explore the dynamic changes in laboratory parameters during the first 10 days after admission and identify early risk indicators for in-hospital mortality in this patient cohort. Methods: Demographics and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Information on the patients was extracted from the electronic medical record, including age, gender, body mass index (BMI), triage oxygen saturation (which was taken on room air), diabetes, hypertension, hyperlipidemia, acute and chronic kidney disease, chronic obstructive pulmonary disease (COPD), and asthma. These patient characteristics were determined a priori as some of the common risk factors associated with COVID-19 mortality from prior literature [ 7 , 27 , 34 ] and were easily obtained from the triage evaluation. The goal of relying on triage data was to implement a triage prediction tool to easily calculate the risk of in-hospital mortality upon patient arrival to the Emergency Department.…”
Section: Methodsmentioning
confidence: 99%
“…Information on the patients was extracted from the electronic medical record, including age, gender, body mass index (BMI), triage oxygen saturation (which was taken on room air), diabetes, hypertension, hyperlipidemia, acute and chronic kidney disease, chronic obstructive pulmonary disease (COPD), and asthma. These patient characteristics were determined a priori as some of the common risk factors associated with COVID-19 mortality from prior literature [ 7 , 27 , 34 ] and were easily obtained from the triage evaluation. The goal of relying on triage data was to implement a triage prediction tool to easily calculate the risk of in-hospital mortality upon patient arrival to the Emergency Department.…”
Section: Methodsmentioning
confidence: 99%
“…Although the majority of symptomatic COVID-19 infections are mild, a subset of patients requires hospitalization due to severe COVID-19 pneumonia, and about 5% of patients develop a critical disease characterized by respiratory failure and/or other organs’ failure [ 2 ]. The early recognition of severe COVID-19 features is crucial to identify patients at risk of poor outcome, create an opportunity for early interventions, personalize the treatment protocols, allow a better allocation of valuable resources, e.g., ventilators and intensive care unit (ICU) beds, and improve the outcomes [ 3 ]. The host factors are the main determinants of the disease severity, although viral factors have also been implicated [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine storms cause life-threatening systemic inflammation characterized by immune cell hyperactivation and the release of proinflammatory cytokines including interleukin-6 (IL-6), interferons, and tumor necrosis factor-alpha (TNF-α) [ 10 ]. Our previous study and several recent articles indicated that a sharp increase in pleiotropic cytokine IL-6 content was associated with acute respiratory distress syndrome (ARDS), sepsis, and even death in patients with COVID-19 [ 11 , 12 ]. IL-6 receptor antagonists have been widely administered in human clinical trials.…”
Section: Introductionmentioning
confidence: 99%